Thrombodynamics Test in Assessing the Risk of Thrombus Formation in Patients with Atrial Fibrillation Taking Direct Oral Anticoagulants - Z. A. Gebekova; I. I. Ivanov; A. Asambayeva; A. I. Skripka; A. A. Sokolova; D. A. Napalkov; T. A. Vuimo (Столичная издательская компания, 2022)
Aim. To evaluate thrombus characteristics in patients with atrial fibrillation (AF) taking different direct oral anticoagulants (DOACs) using Thrombodynamics test.Materials and methods. Thrombodynamics test was performed in 100 patients with paroxysmal and permanent forms of AF taking different DOACs, dose choice was done in accordance with the instructions for drugs use. For analysis samples of fresh citrated platelet-free plasma were taken just before regular DOACs dose intake (trough concentration). Statistical data processing was carried out using R software packages.Results. All patients had no history of thrombosis or bleeding before inclusion in this study. All parameters of Thrombodynamics test taken at residual concentration of DOACs were in general within reference values, that is in the area of normal coagulation: spatial clot growth rate (V) - 26.56 (25.0; 29.2) μm/min, the time to the start of clot growth (Tlag) - 1.05 (0.85; 1.27) min, initial spatial clot growth rate (Vi) - 44.3±7.7 μm/min, stationary spatial clot growth rate (Vst) - 26.5 (24.9; 28.4) μm/min, clot size (CS) - 999.7 (912.9; 1084.7) μm, clot density (D) - 22883.1±3199.9 arb. units. D was appeared to be higher in women [22947.7 (21477.5; 22947.7) vs men [22124.8 (19722.8; 22124.8), p=0.035] and Tlag was significantly higher in patients with chronic heart failure [1.2 (1.0; 1.2) vs 1.0 (0.8; 1.0), p=0.008]. A correlation was found between level of creatinine and Tlag parameter, glomerular filtration rate (GFR) and clot density. With an increase in the level of creatinine in the blood and a decrease in GFR, respectively, there was an increase in Tlag parameter (p-value 0.038); with an increase in GFR, clot density decrease (p-value 0.005).Conclusion. All parameters of Thrombodynamics test on residual concentration of DOACs were within reference values that indicated optimal anticoagulant effect of all DOACs. The obtained data of normal coagulation at the residual concentration of the anticoagulant are consistent with the previously obtained data on the safety and effectiveness of DOACs using other methods. Further studies with clinical end points are needed to assess the clinical value of this method.